Estrongiloidíase em pacientes com pênfigo foliáceo - José Tavares-Neto; Denise Barcelos Alves; José Umberto Franciscon; Carlos Roberto S. Serrano (Sociedade Brasileira de Medicina Tropical (SBMT), 1991)
Em 30 pacientes com pênfigo foliáceo, a freqüência da estrongiloidíase foi de 40,0%, através de três exames de Baermann-Moraes. No "Hospital do Pênfigo", em Uberaba, as freqüências da estrongiloidíase nos funcionários (n = 14) e escolares (n = 47) da Escola-creche, anexa, também foram altas, respectivamente 35,7% e 23,4%. Em 7 (58,3 %) das 12 amostras do solo, do jardim/pátio do "Hospital", foram observadas formas de vida livre do Strongyloides stercoralis. O fator ambiental e a predisposição dos pacientes foram associados à alta transmissão da estrongiloidíase. In 30 patients with foliaceous pemphigus the frequency of strongyloidiasis was 40%, by three Baermann- Moraes examination. In the "Hospital do Penfigo", for patients with pemphigus of Uberaba, the frequencies of strongyloidiasis in the employees (n = 14) and students (n=47), of the annexed nursery, also were high, respectively 35.7 % and 23.4%. In 7(58.3) of 12 samples from the soil of the hospital courtyard were found free-life forms of Strongyloides. The environmental factor and the susceptibility of the pacients were associated with the high transmission of the strongyloidiasis.